Gender, residence, and socioeconomic differences in the relationship of nutrition literacy with vegetable and fruit intake in adults - Tian, Xi; Hu, Xiaoting; Sun, Yuhui; Liu, Huaqing (Frontiers in Nutrition, 2025)
BackgroundIntake of vegetable and fruit is vital for long-term health outcomes. Nutrition literacy (NL) is an important influencing factor of dietary habits. This study aims to explore the relationship between NL and vegetable and fruit intake.MethodsA cross-sectional survey was conducted in Bengbu, China. Ordinal logistic regression was utilized to explore the correlation between NL and intake of vegetable and fruit, reporting odds ratios (OR) and 95% confidence intervals (CI).ResultsApproximately 71.0, 40.4, and 40.0% of participants reported consistent consumption of dark-colored vegetables, light-colored vegetables, and fruit, respectively. Individuals with the highest NL were 53% more likely to consume dark-colored vegetables (OR = 1.53, 95% CI:1.13–2.09), 34% more likely to consume light-colored vegetables (OR = 1.34, 95% CI: 1.03–1.75), and 200% more likely to consume fruit (OR = 3.00, 95% CI: 2.29–3.94) than those with the lowest NL. In subgroup analyses, the association of NL with dark-colored vegetables intake was observed among females, urban residents, non-farmers and those with high monthly income. Additionally, the relationship between NL and light-colored vegetables intake was revealed among non-farmers. Conversely, the correlation of NL with fruit intake was exhibited in those had a monthly income < 1,000 RMB and had a monthly income of 1,000–3,000 RMB.ConclusionThis study found a positive relationship between NL and vegetable and fruit intake. However, this relationship exhibited variations based on gender, residence, and socioeconomic status. Public health practitioners should tailor nutrition intervention programs to improve vegetable and fruit consumption among adults in the studied region, with a particular focus on females, urban residents, and individuals with high monthly incomes.